Biological activity of Acinetobacter calcoaceticus IMV B-7241 surfactants synthesized in the presence of competitive bacteria Bacillus subtilis BT-2 - Pirog, Tatiana; Ivanov, Mykyta; Shevchuk, Tetiana (My University, 2023)
Currently, the effectiveness of technologies of microbial surfactant, which are characterized by a complex of practically valuable physicochemical and biological properties, is lower than that of synthetic analogues. To reduce the cost of these products of microbial synthesis, industrial waste is used as substrates for their biosynthesis. In previous studies, it was established that surfactants synthesized by Acinetobacter calcoaceticus IMV B-7241 on crude glycerol had lower antimicrobial activity compared to those obtained on purified glycerol. The main approaches to the regulation of the biological activity of microbial surfactants are their post-fermentation chemical modification, as well as the improvement of producer strains by methods of metabolic and genetic engineering. In recent years, the great amount of studies have appeared on the co-cultivation of producers of antimicrobial compounds with competitive microorganisms (biological inductors), in response to the presence of which the antimicrobial activity of the final product increases. Aim. To study the effect of live and inactivated cells of Bacillus subtilis BT-2, as well as the corresponding supernatant, on the antimicrobial, anti-adhesive activity and the ability to destroy biofilms of A. calcoaceticus IМV B-7241 surfactants, synthesized in a medium with glycerol of different degrees of purification. Methods. The IMV B-7241 strain was grown in the liquid mineral medium with purified and crude glycerol, into which live and inactivated B. subtilis BT-2 cells, as well as the supernatant after growing the BT-2 strain (2.5−10%, v/v) were added. Surfactants were extracted from the supernatant of the culture liquid with Folch's mixture. Anti-adhesive activity and the degree of destruction of biofilms were determined by the spectrophotometric method, antimicrobial activity − by the indicator of the minimum inhibitory concentration. The activity of enzymes of surface-active aminolipids biosynthesis (NADP+-dependent glutamate dehydrogenase) and glycolipids (phosphoenolpyruvate (PEP)-carboxylase, PEP-synthetase, PEP-carboxykinase, trehalose-phosphate synthase) was analyzed in cell-free extracts obtained after сells sonication. Results. It was established that the introduction of inactivated B. subtilis BT-2 cells and supernatant into the medium with both substrates did not affect the indicators of the surfactants synthesis, while in the presence of live cells of the BT-2 strain in the medium with purified glycerol, a decrease in the concentration of the final product by 1.5 times, and in the culture medium with crude glycerol - an increase of 1.4 times were observed compared to the indicators without the inductor. The study of the antimicrobial activity of surfactants showed that the most effective of the used inductors (live, inactivated cells, supernatant) were live cells of B. subtilis BT-2. The introduction of BT-2 strain live cells into the culture medium with both substrates was accompanied by the formation of surfactants, the minimum inhibitory concentrations of which in relation to bacterial (Bacillus subtilis BT-2, Staphylococcus aureus BMS-1, Proteus vulgaris PA-12, Enterobacter cloacae С-8 ) and yeast (Candida albicans D-6, Candida tropicalis PE-2) test-cultures were 3-23 times lower than established for those synthesized on the medium without this inductor. Anti-adhesive activity of surfactants obtained on purified and crude glycerol in the presence of all types of inductors was higher than those synthesized in the culture medium without inductors (cells adhesion of bacterial and yeast test-cultures on polyvinyl chloride was 13−70 and 33−96%, respectively). Introduction into A. calcoaceticus IMV B-7241 medium cultivation of both live and inactivated B. subtilis BT-2 cells, as well as the supernatant, was accompanied by the synthesis of surfactants in the presence of which the disruption of bacterial biofilms was on average 10-20 % higher compared to using surfactants synthesized without an inductor. In the presence of B. subtilis BT-2 in the medium, in the cells of the IMV B-7241 strain the activity of NADP+-dependent glutamate dehydrogenase (a key enzyme of aminolipids biosynthesis) increased by 1.5-2 times, while the activity of glycolipids enzymes biosynthesis remained practically at the same level as without an inductor. Such data indicated that the higher biological activity of surfactants obtained by A. calcoaceticus IMV B-7241 in the presence of biological inductors might be due to an increase in the content of aminolipids in their composition. Conclusions. As a result of research, it was established the possibility of regulating the antimicrobial and anti-adhesive activity, as well as the ability to disrupt biofilms of A. calcoaceticus IМV B-7241 surfactants by introducing into the culture medium of competitive bacteria B. subtilis BT-2. It is important that under such cultivation conditions the antimicrobial activity of surfactants synthesized on toxic crude glycerol significantly increased.
Keywords: мікробні поверхнево-активні речовини; біологічна активність; конкурентні мікроорганізми; кафедра біотехнології і мікробіології; microbial surfactants; biological activity; competitive microorganisms